Correlation of antimicrobial fraction unbound and sieving coefficient in critically ill patients on continuous renal replacement therapy: a systematic review. (19th November 2021) - Farrar, Julie E.; Mueller, Scott W.; Stevens, Victoria; Kiser, Tyree H.; Taleb, Sim; Reynolds, Paul M.
Abstract: Background: Fraction unbound has been used as a surrogate for antimicrobial sieving coefficient (SC) to predict extracorporeal clearance in critically ill patients on continuous renal replacement therapy (CRRT), but this is based largely on expert opinion. Objectives: To examine relationships between package insert-derived fraction unbound (Fu-P ), study-specific fraction unbound (Fu-S ), and SC in critically ill patients receiving CRRT. Methods: English-language studies containing patient-specific in vivo pharmacokinetic parameters for antimicrobials in critically ill patients requiring CRRT were included. The primary outcome included correlations between Fu-S, Fu-P, and SC. Secondary outcomes included correlations across protein binding quartiles, serum albumin, and predicted in-hospital mortality, and identification of predictors for SC through multivariable analysis. Results: Eighty-nine studies including 32 antimicrobials were included for analysis. SC was moderately correlated to Fu-S (R 2 = 0.55, P < 0.001) and Fu-P (R 2 = 0.41, P < 0.001). SC was best correlated to Fu-S in first (<69%) and fourth (>92%) quartiles of fraction unbound and above median albumin concentrations of 24.5 g/L (R 2 = 0.71, P = 0.07). Conversely, correlation was weaker in patients with mortality estimates greater than the median of 55% (R 2 = 0.06, P = 0.84). SC and Fu-P were also best correlated in the first quartile of antimicrobial fraction unbound (R 2 = 0.66, P < 0.001). Increasing Fu-P, flow rate, membrane surface area, and serum albumin, and decreasing physiologic charge significantly predicted increasing SC. Conclusions: Fu-S and Fu-P were both reasonably correlated to SC. Caution should be taken when using Fu-S to calculate extracorporeal clearance in antimicrobials with 69%–92% fraction unbound or with >55% estimated in-hospital patient mortality. Fu-P may serve as a rudimentary surrogate for SC when Fu-S is unavailable.